2023
DOI: 10.1128/spectrum.04084-22
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Bamboo Fiber Improves Productive Performance by Regulating Gut Microbiota and Inhibiting Chronic Inflammation of Sows and Piglets during Late Gestation and Lactation

Abstract: Dietary fiber is widely applied in the nutrition of sows due to its potential value in improving performance and intestinal health. Fermented bamboo fiber, rich in dietary fiber, has not been fully evaluated to be used in sow diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Positively charged NPs assemble more readily on the cell surface than negatively charged ones because of electrostatic attraction. In contrast, negatively charged NPs can pass through the plasma membrane by forming potent covalent bonds [ 2 ]. The out-comes of the present study suggest that electrostatic repulsion may be overcome by smaller particles, regardless of charge, and that the difference in the metal ion gradient between, within and outside the cell may be a critical factor in internalization of NPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positively charged NPs assemble more readily on the cell surface than negatively charged ones because of electrostatic attraction. In contrast, negatively charged NPs can pass through the plasma membrane by forming potent covalent bonds [ 2 ]. The out-comes of the present study suggest that electrostatic repulsion may be overcome by smaller particles, regardless of charge, and that the difference in the metal ion gradient between, within and outside the cell may be a critical factor in internalization of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Young D. asper shoots are sweet in taste and sold in canned or vacuum-packed packets [ 1 ]. Bamboo shoots can also be used to extract high-quality fiber for modern textile and clothing industries [ 2 ]. However, for continuous bamboo supply, new and sustainable propagation methods with reduced proliferation period are necessary to meet industrial demands.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that improved health conditions, such as increased contents of immunoglobulins and decreased levels of proinflammatory factors, are beneficial to sows' reproductive performance [ 33 ]. Moreover, increase in fatty acid content in colostrum and milk also favors the growth performance of lactating piglets [ 34 36 ]. Therefore, we can reasonably deduce that the increase in number born alive per litter might be due to the improved health condition of sows fed laminarin-contained diets.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also found in pigs. A high-fiber diet reduced proinflammatory markers like IL-6 and increased the anti-inflammatory markers like IL-10 in sows and piglets through promoting beneficial bacteria and the production of SCFAs ( 247 249 ). However, studies that investigated the therapeutic effects of dietary fiber in HDP and preterm birth are still lacking.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%